Analisis Financial Distress Dengan Metode Zmijewski Pada Koperasi Simpan Pinjam Di Wilayah Kabupaten Sikka - Veronika Ursula Kego; Wilhelmina Mitan; Paulus Libu Lamawitak (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the financial condition of credit cooperatives in the Puskopdit Swadaya Utama area experiencing potential financial distress in 2019-2021 using the Zmijewski method. The method of analysis in this study is accounting analysis in the form of the Zmijewski method. Data collection techniques in the form of literature studies and documentation. The data analysis technique in this study uses quantitative descriptive analysis using the Zmijewski method. The results show that credit cooperatives under the auspices of the Primary Swadaya Puskopdit based on X-Score calculations in the Zmijewski method in 2019, 2020, 2021 state that the financial distress zone is larger than the non-financial distress zone. financial distress. Research on 14 savings and loan credit cooperatives (KSP) under the auspices of the Maumere Swadaya Utama Puskopdit shows that there are 2 savings and loan cooperatives (KSP) that are included in the healthy zone (non-financial distress) and there are 9 savings and loan credit cooperatives (KSP) that are included in the bankruptcy zone (financial distress) in three consecutive years, namely 2019, 2020 and 2021.